Vibrational spectroscopic study of intensities and shifts of symmetric vibration modes of ozone diluted by cumene - Heidari, A.; Brown, C. (International Journal of Advanced Chemistry, 2016)
In the current research, ATR–FTIR and FT–Raman spectroscopies was used to investigate the effect of concentration on IR and Raman intensities and shifts of symmetric vibration modes of Ozone diluted by Cumene. The symmetric vibration mode of Ozone was observed at IR and Raman shifts of 850 and 975 cm-1, respectively. By reducing the concentration of Ozone, its intensity also was reduced and the symmetric vibration mode of Cumene was observed at IR and Raman shifts of 1050 and 1185 cm-1, respectively. The concentration has not influence on IR and Raman shifts of vibration modes. The experimental results were confirmed the linear dependency of IR and Raman intensities to the concentration of sample.Ozone molecule (left illustration) and Cumene molecule (right illustration) (Santiago-López et al. 2010; Guevara-Guzmán et al. 2009; Pereyra-Muñoz et al. 2006; Foucaud et al. 2006; Elsayed 2001; van Hoof et al. 1997; Chrostowski et al. 1983; Boehme et al. 1992; Catalá et al. 2013; Balvers et al. 1992; Marker et al. 1986).